Partisan Punitive Practice in Varėna District (1944–1952) - Mikelevičius , Laimis (Genocidas ir rezistencija, 2013)
One of the least analysed aspects of the partisan war in Lithuania between 1944 and 1953 is the punitive practice of partisans. The aim of Total Irreversible Human Loss in Lithuania Between 1944 and 1953, a programme conducted by the Special Investigation Department of the Genocide and Resistance Research Centre of Lithuania, is to explore in detail the relationship between the partisans and the population during the war, to reveal the variety of executions conducted by partisans, and to clarify the decision-making procedures of partisan organisations with respect to the population. The objectives of the programme are to carry out a complex historical-statistical study and to prepare a classification of cases and a statistical data set; to collect data on the relationship of partisan organisations with the population and on the activities of courts-martial and other partisan institutions; and to carry out historical and legal analysis of data and to assess the legitimacy, validity and effects of partisan decisions concerning the population. It is also necessary to clarify, supplement and correct errors in the Soviet era card files that are stored at the Genocide and Resistance Research Centre and serve as the database for people killed and injured by partisans. This article has been prepared on the basis of the study of death sentences, executions, and people killed in action by partisans in the period 1944–1952 in the district of Varėna, the area of former Varėna County. During the archival-historiographic study, cases of killings were examined in detail through the exploration of the circumstances, motives, and other information. An important part of the study was the analysis of partisan documents: court-martial reports, various proclamations, and warnings. The most serious areas of the punitive practices of partisans were also discussed: killings of families or minors, issues of guilt and innocence, and the circumstances of partisan warfare at the time. Between 1944 and 1952, 688 people were killed in the district of Varėna; a total of 858 recorded cases of executions or possible executions were studied. The social status of 497 victims and dates of birth of 443 victims were identified. The average age of victims was 35.6 years. Three main categories of victims can be identified: employees and officers of military and security forces (29.6%), Soviet administrative staff and employees (20.9%), and farmers and workers (a total of 30.6%; 22.1% and 8.5% respectively). Other categories by job, occupation, etc.: family members of employees of military and security organisations (2%), family members of administrative staff (4.8%), settlers (3%), informers and agents (3.2%), Soviet activists (2.8%), family members of activists (0.2%), members of Komsomol (0.8%), students (0.2%), and former partisans and people who were close to them (1.8%). Eighty convictions by partisan courts-martial were identified, and 23 other partisan documents (warnings, proclamations) were left at the places of execution. This accounts for 14.9% of all executions. Most soldiers, employees and officers of military and security forces perished or were executed in an ambush. The justification for killing Soviet administrative officials, employees, and other staff members was usually that those people were carrying out Soviet orders. Usually executions were carried out at people’s homes or outside homes and by giving a warning and providing a charge. Death penalties and executions of farmers and workers pose the most questions. Most are executions for collaboration with the Soviets and the sabotage of the partisan movement. Based on the information collected, it is however usually difficult to fully assess the legitimacy of such killings.